MEDIA KOMMUNIKATSIYALARDA MATN KREOLIZATSIYASINING O’ZARO TA’SIR MEXANIZMLARI VA ASOSIY USULLARI - Raximjonov Doniyor Shuxratilla o‘g‘li; Nurbek Gulimmatov Murodboyevich (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Background: Creolized texts combine verbal and non-verbal semiotic assets into unified operational units.However, the precise structural linkages and coding methods that govern this integration require systematic classification. Objective: This paper identifies and classifies the core interaction mechanisms and practical methods of creolization that shape modern English-language media communications. Methods: A systemic structural analysis was conducted on multimodal messaging strategies, focusing on the interface mechanics between verbal tracks and visual graphics. Results: The study outlines five main interaction mechanisms:complementarity, redundancy, anchoring, relay, and contrast. It isolates key operational methods including image-text integration, typography as a sign, visual metaphor, and color framing. Conclusion: Successful text creolization requires balancing semantic richness with clarity to avoid cognitive overload, maximizing the functional affordances of each mode.